1998
DOI: 10.1044/jslhr.4104.887
|View full text |Cite
|
Sign up to set email alerts
|

Communication Between Deaf Children and Their Hearing Mothers

Abstract: In the present longitudinal study, 20 deaf and 20 hearing children were observed during free play with their hearing mothers when the children were 22 months and 3 years of age. Compared to hearing children, deaf children were severely language delayed, with deaf 3-year-olds using less language (speech or sign) than hearing 22-month-olds. Deaf children communicated primarily through nonlinguistic vocalizations, with increasing use of gesture from 22 months to 3 years of age. Although mothers of deaf children u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 23 publications
3
38
0
2
Order By: Relevance
“…The results suggest that the use of signs with deaf children does not prevent them from developing speech. This supports other research findings, which showed that early experience with sign language might be expected to have positive effects on spoken language development, regardless of hearing status (Schlesinger & Meadow, 1972;Gardner & Zorfass, 1983;Lederberg & Everhart, 1998;van den Bogaerde &Baker, 2001). Moreover, if deaf parents are bilingual they can help their deaf children develop communicative competence in both the sign language and the Polish language.…”
Section: Discussionsupporting
confidence: 75%
“…The results suggest that the use of signs with deaf children does not prevent them from developing speech. This supports other research findings, which showed that early experience with sign language might be expected to have positive effects on spoken language development, regardless of hearing status (Schlesinger & Meadow, 1972;Gardner & Zorfass, 1983;Lederberg & Everhart, 1998;van den Bogaerde &Baker, 2001). Moreover, if deaf parents are bilingual they can help their deaf children develop communicative competence in both the sign language and the Polish language.…”
Section: Discussionsupporting
confidence: 75%
“…These aspirations had their effect on the study of child development within the field of Deaf Studies. Whereas research before the era of CI was mainly concerned with interaction and successful communication (Meadow, 1981;Wedell-Monnig & Lumley, 1980;Lederberg & Mobley, 1990;Koester, 1995;Lederberg & Everhart, 1998;Harris & Mohay, 1997; for a review see Meadow-Orlans, 1997), after the turn of the millennium investigators became primarily interested in describing and detailing the development of spoken language as a function of improved auditory perception (Niparko et al, 2010;Nicholas & Geers, 2007;Nikolopoulos et al, 2004;Svirsky, Teoh et al, 2004;Svirsky, Robbins et al, 2000;Geers, 2003Geers, , 2004Geers, , 2006; for a review see Vlastarakos et al, 2010). More recently still, attention has been focussed on the effect of age of implantation on speech intelligibility and auditory perception (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Deaf children have extensive difficulties with the reproduction of language in general (Lederberg and Everhart 1998). The use of CIs at younger ages has improved the amount of vocalisation and language acquired (Ertmer and Mellon 2001;Hammes et al 2000).…”
Section: Reproduction Of Songmentioning
confidence: 97%